PENGEMBANGAN MEDIA EDUKASI GIZI MELALUI BUKU MEWARNAI UNTUK PESERTA PENDIDIKAN ANAK USIA DINI (PAUD) (MEDIA DEVELOPMENT OF NUTRITION EDUCATION THROUGH COLORING BOOKS FOR EARLY CHILDHOOD EDUCATION (ECD)) - Yurista Permanasari; Erna Luciasari; Aditianti Aditianti (Persagi, 2013)
ABSTRACT Early childhood education (ECD) is a right time to provide nutrition education. The education can be given through playing patterns suitable for age 2-6 years. Currently there is no active nutrition education media for ECD participants. Therefore it is necessary to develop an active media of nutrition education through colouring book. Colouring activitities can stimulate both the cognitive and motor development of children. This study aimed to develop a colouring book as a nutrition education media for ECD participants and assess the acceptance of the media. This research is a formative study using qualitative design. The sample in this study was children aged 2-6 years, their parents, and teachers from four selected ECD in the city and district of Bogor. The research was conducted in 2 steps. The first step was baseline data collection through observations, group interviews and in-depth interviews to the children, the parents, and the teachers of ECD. Based on the baseline data, the nutrition education materials was prepared and the colouring book was designed. The second step was the assessment of the acceptance and the application of educational media by observing the use of educational media while teachers provided the material in the ECD classroom and the use of colouring books by ECD participants. A group interview was also conducted to see the teacher’s response of the nutrition education media through colouring books, and to find qualitative change in nutrition knowledge of ECD participants. Education materials through colouring books were made in two versions. First version is the books purposed for group A of ECD (< 4 years) and second version is for group B of ECD (4-6 years). After the teacher provided the nutrition education materials, nutritional knowledge of ECD participants was better than before. In addition, the media play as an atractive teaching material that stimulated children’s interest. Colouring books can be used as an educational media to increase nutrition knowledge of the children. Keywords: nutrition education media, colouring books, Early Childhood Education ABSTRAK Mendidik anak pada usia dini merupakan saat yang tepat untuk memberikan pendidikan gizi melalui pola bermain yang sesuai dengan usia 2 - 6 tahun. Saat ini belum ada media edukasi gizi aktif untuk peserta PAUD (Pendidikan Usia Dini). Oleh karena itu perlu dikembangkan media edukasi gizi aktif berupa media mewarnai yang juga dapat merangsang aspek kognitif dan motorik anak. Penelitian ini bertujuan untuk mengembangkan buku mewarnai sebagai media edukasi gizi untuk peserta PAUD, dan menilai daya terima media tersebut. Penelitian ini merupakan studi formatif dengan desain kualitatif. Sampel penelitian adalah anak usia 2-6 tahun, orang tua, dan guru di empat PAUD terpilih di Kota dan Kabupaten Bogor. Pelaksanaan penelitian dilakukan dalam 2 tahap. Tahap pertama yaitu pengumpulan data dasar dengan observasi, wawancara kelompok dan wawancara mendalam kepada anak dan orang tua peserta PAUD, serta guru PAUD. Berdasarkan data dasar tersebut, kemudian dilakukan penyusunan materi edukasi gizi dan perancangan buku mewarnai. Tahap kedua adalah penilaian daya terima dan aplikasi media edukasi dengan mengobservasi penggunaan media edukasi pada saat pemberian materi oleh guru PAUD di kelas, dan penggunaan media buku mewarnai oleh anak peserta PAUD. Selain itu juga dilakukan wawancara kelompok untuk melihat respon guru terhadap media edukasi gizi melalui buku mewarnai, dan wawancara kelompok peserta PAUD untuk mengetahui perubahan pengetahuan gizi secara kualitatif. Materi edukasi dengan buku mewarnai ini dibuat dalam dua versi yaitu untuk PAUD kelompok A (< 4 th) dan kelompok B (4-6 th). Pengetahuan gizi anak peserta PAUD menjadi lebih baik setelah pemberian materi edukasi gizi dengan buku mewarnai. Selain itu, media ini berperan sebagai bahan ajar menarik yang menstimulasi minat anak. Buku mewarnai dapat digunakan sebagai media edukasi untuk menambah pengetahuan gizi anak dengan cara mewarnai gambar. [Penel Gizi Makan 2013, 36(1):31-43] Kata kunci: Media Edukasi Gizi, Buku Mewarnai, Pendidikan Anak Usia Dini